Effects of Skeletally Supported Anterior en Masse Retraction with Varied Lever Arm Lengths and Locations in Lingual Orthodontic Treatment: A 3D Finite Element Study. (17th May 2021) - Ghannam, Mohammad; Kamiloğlu, Beste
Abstract : Objective . This study is aimed at analyzing different points of force application during miniscrew supported en masse retraction of the anterior maxillary teeth to identify the best line of action of force in lingual orthodontic treatment. Materials and Methods . Three-dimensional (3D) finite element models were created to stimulate en masse retraction with different heights and positions of the miniscrew and lever arm to change the force application points; a 150 g retraction force was applied from the miniscrew to the lever arms, and the initial tooth displacements were analyzed. Results . Lingual crown tipping and occlusal crown extrusion were seen at all heights and positions of the miniscrew and lever arm, but when the miniscrew height was at 8 mm and the power arm was located between the lateral incisors and canines, these tipping patterns were less than those obtained with a 4.5 mm high miniscrew and a lever arm located distal to the canines. Conclusion . All miniscrew heights and lever arm positions showed initial lingual crown tipping and labial root tipping with occlusal crown extrusion. However, the 8 mm miniscrew height and the lever arm located between the lateral incisor and canine showed fewer amounts of these tipping patterns than a 4.5 mm miniscrew height and lever arm located distal to the canines. Therefore, this could be the preferred point of force application during en masse retraction in lingual treatment with additional torque control methods.